1995
DOI: 10.1093/brain/118.3.597
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome in northern China Relationship to Campylobacter jejuni infection and anti-glycolipid antibodies

Abstract: Guillain-Barré syndrome has been considered to be primarily an acute inflammatory demyelinating polyneuropathy (AIDP). Our experience with Guillain-Barré syndrome in northern China differs from the traditional concept. Electrophysiologically and pathologically, most of our patients have motor axonal degeneration with minimal cellular inflammation, which we have termed 'acute motor axonal neuropathy' (AMAN). The current studies were undertaken to characterize prospectively the clinical, electrophysiological, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
644
6
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 722 publications
(690 citation statements)
references
References 0 publications
34
644
6
6
Order By: Relevance
“…Until mid 80's the acute poliomyelitis was the main cause of acute flaccid palsies but with the program of eradication of poliomyelitis had emerged the Guillain-Barré syndrome (GBS) as the major etiology, such statement is already proved in the developed countries, but still unknown in many communities. The epidemiological data has been shown valuable in evaluating the frequency of GBS in various populations, studying changes in incidence over time, detecting outbreaks or cluster of unusual preceding illnesses, and possible illuminating underlying causes 1,2 . Epidemiological surveillance of GBS is considerable relevant since large and small epidemics due to vaccines, water pollution, drugs, as well unexpected statistically significant variations in annual incidence in age sub-groups have been reported 3 .…”
mentioning
confidence: 99%
“…Until mid 80's the acute poliomyelitis was the main cause of acute flaccid palsies but with the program of eradication of poliomyelitis had emerged the Guillain-Barré syndrome (GBS) as the major etiology, such statement is already proved in the developed countries, but still unknown in many communities. The epidemiological data has been shown valuable in evaluating the frequency of GBS in various populations, studying changes in incidence over time, detecting outbreaks or cluster of unusual preceding illnesses, and possible illuminating underlying causes 1,2 . Epidemiological surveillance of GBS is considerable relevant since large and small epidemics due to vaccines, water pollution, drugs, as well unexpected statistically significant variations in annual incidence in age sub-groups have been reported 3 .…”
mentioning
confidence: 99%
“…5 In Taiwan Lyu RK et al showed seasonal preponderance evident between March to May. 13 McKhann also found most cases of GBS occurring during the summer month and among children and young adult, most of which reside in rural area.…”
Section: Resultsmentioning
confidence: 97%
“…This observation is similar to study conducted by Ho et al and McKhann in China which also showed that more than half of the cases of Guillain Barre syndrome came from rural area. 5,14 The cause of its rural predominance is not known. It may be because of high incidence of respiratory, gastrointestinal illness, which goes untreated in rural area because of lack of awareness and unavailability of medical facility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMAN and AMSAN cases were originally described in northern China and are associated with Campylobacter Jejuni (C. Jejuni) infection, which is a poor prognostic factor [26]. Patients with AMAN have a rapid progression of weakness to an early nadir over a few days resulting in prolonged paralysis and respiratory failure [27].…”
Section: Gbs Variantsmentioning
confidence: 99%